2021
DOI: 10.1016/s2468-2667(21)00065-7
|View full text |Cite|
|
Sign up to set email alerts
|

Spatial, temporal, and demographic patterns in prevalence of chewing tobacco use in 204 countries and territories, 1990–2019: a systematic analysis from the Global Burden of Disease Study 2019

Abstract: Background Chewing tobacco and other types of smokeless tobacco use have had less attention from the global health community than smoked tobacco use. However, the practice is popular in many parts of the world and has been linked to several adverse health outcomes. Understanding trends in prevalence with age, over time, and by location and sex is important for policy setting and in relation to monitoring and assessing commitment to the WHO Framework Convention on Tobacco Control. Methods We estimated prevalenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 37 publications
6
24
0
Order By: Relevance
“…In 2019, there were an estimated 155 million smokers aged between 15 and 24 years -equivalent to 20.1% of young men and 5.0% of young women, globally. Two-thirds (65.5%) of all current smokers began smoking by age 20, and 89% of smokers began by age 25, highlighting a critical age window during which individuals develop nicotine addiction and transition to become established smokers [14][15][16].…”
Section: Prevalence Of Smoking and Youth Vapingmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2019, there were an estimated 155 million smokers aged between 15 and 24 years -equivalent to 20.1% of young men and 5.0% of young women, globally. Two-thirds (65.5%) of all current smokers began smoking by age 20, and 89% of smokers began by age 25, highlighting a critical age window during which individuals develop nicotine addiction and transition to become established smokers [14][15][16].…”
Section: Prevalence Of Smoking and Youth Vapingmentioning
confidence: 99%
“…Turkey, Jordan, and Zambia had the largest increases in number of young female smokers. Over half of countries, worldwide, showed no progress in reducing smoking among 15-24 years old [14][15][16].…”
Section: Prevalence Of Smoking and Youth Vapingmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Deng et al explored the geographic and temporal trends of CRC disease burden related to various dietary factors, and found that from 1990 to 2019, CRC deaths and DALYs caused by dietary factors increased by half, and interventions for alterable dietary risk factors would reduce CRC deaths and DALYs by 32 and 34%, respectively (15). In recent years, the prevalence of smoking (16) and drinking (17) has shown a downward trend or has changed little globally, while the prevalence of high BMI (18) and LPA (19) has shown an upward trend in some regions. Understanding the geographic and temporal trends and its influencing factors of CRC disease burden caused by LPA and high BMI will make the formulation of CRC prevention and control policies more targeted.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review showed that alcohol use disorders have a prevalence of 1320.8 cases per 100 000 people. As per WHO estimates, 20.2% of the world's population aged 15 years or more are current smokers, and 4.7% of world's population use smokeless tobacco (Kendrick et al, 2021; Reitsma et al, 2021). The prevalence of Internet gaming disorder is reported to be 2.47% (Pan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%